2001
DOI: 10.1046/j.1442-2042.2001.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of androgen‐independent prostate cancer with dexamethasone: A prospective study in stage D2 patients

Abstract: Purpose: In order to evaluate the efficacy of dexamethasone in the treatment of Japanese men with androgen-independent prostate cancer, a prospective study was conducted using prostate-specific antigen (PSA) as a primary end-point. Methods: Nineteen Japanese men with stage D2 androgen-independent prostate cancer were registered and treatment was started. After ruling out anti-androgen withdrawal syndrome, they were treated with dexamethasone (1.5 mg daily). Patients were monitored for PSA, symptoms, radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
(30 reference statements)
2
23
0
Order By: Relevance
“…Both prednisone (101) and dexamethasone (102,103) have shown some antitumor activity in patients with AIPC, but the mechanisms responsible for their effects are not fully known. Dexamethasone treatment, however, is known to affect IB␣ and IL-6 regulation in multiple myeloma, a cancer that is highly sensitive to bortezomib (104), and both these mechanisms may be important in prostate cancer (48).…”
Section: Introductionmentioning
confidence: 99%
“…Both prednisone (101) and dexamethasone (102,103) have shown some antitumor activity in patients with AIPC, but the mechanisms responsible for their effects are not fully known. Dexamethasone treatment, however, is known to affect IB␣ and IL-6 regulation in multiple myeloma, a cancer that is highly sensitive to bortezomib (104), and both these mechanisms may be important in prostate cancer (48).…”
Section: Introductionmentioning
confidence: 99%
“…Reported effects are linked to decreased prostate specific antigen levels and amelioration of symptoms 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A PSA response, with a reduction >50%, was seen in 5 of those patients (27.8%). 45 Another retrospective study from the Mayo Clinic reported a PSA reduction >50% in 23 of 38 patients (61%) who were treated with dexamethasone. 43 The combination of dexamethasone with calcitriol may provide additive benefit, based on data from preclinical models.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported the positive clinical effects of dexamethasone in patients with prostate cancer. [43][44][45] In 1 study, 19 patients with HRPC were treated prospectively with 1.5 mg of dexamethasone daily. A PSA response, with a reduction >50%, was seen in 5 of those patients (27.8%).…”
Section: Discussionmentioning
confidence: 99%